Utilization of Short Stories as Educational Media "Stop Bullying" for Students of UPT SPF SD Inpres Unggulan Toddopuli Makassar: Pemanfaatan Cerpen Sebagai Media Edukasi “Stop Bullying” Terhadap Siswa UPT SPF SD Inpres Unggulan Toddopuli Makassar - Soraya, Andi Inayah; Khaerana, A. ST. Aldilah; Ramadhani, Rezky; Ismail, Nur Syamsu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
UPT SPF SD Inpres Unggulan Toddopuli is one of the strategical schools in Makassar City due to its location which is near to various public fasilities. Therefore, this school is in great demand by the community. Being in great demand by the community becomes one of the factors for the high level of heterogeneity of family backgrounds and behavior patterns of its students. This situation often triggers friction between individuals in the form of bullying between students both among themselves and between grade levels. The lack of knowledge of students and teachers about bullying is one of the reasons this behavior still often occurs in the school environment. Many students have become perpetrators and victims but they do not realize it. Based on this fact, the team of Community Service Program finds the potential of utilizing literary work namely short story as an educational medium to campaign “Stop Bullying” to the students at UPT SPF SD Inpres Unggulan Toddopuli. The method that applied in this community service was field observation that consists of some activities. Firstly, the students were given a pre-test to find out the students’ knowledge about bullying. Then, the students were given the chance to read and to review some short stories which contain the information about bullying. Lastly, the post-test was given to the students to measure the improvement of the students’ knowledge about bullying. The descriptive analysis of the questionnaire data shows that there is an increase on the students’ knowledge about bullying after reading and reviewing the short stories. It is also found that the students are happy to get knowledge about bullying through the short stories because they provide the stories which relevant to the students’ daily lives so that they are easy to understand and fun. Furthermore, the Community Service team also socialized the information about bullying. In addition, the team also created a draft of team that consists of teachers who will be in charge for handling bullying in the school and the programs that should be conducted in an effort to educate the teachers sustainably about the dangers of bullying.